Readiness of Students to Become School Counselor - Yesi Novita Sari; Yarmis Syukur (Consilium, 2021)
This research is motivated by the phenomenon of students who do not have the readiness to become Guidance and Counseling teachers. This is due to the lack of personal qualities that must be possessed by students as prospective Guidance and Counseling teachers. Students as prospective Guidance and Counseling teachers are required to facilitate quality personal development and can be accounted for professionally. This study aims to describe the readiness of students to become guidance and counseling teachers. This research is a descriptive type of research with quantitative methods. The study population consisted of 141 FIP UNP Guidance and Counseling students for the semester of July-December 2019, batch 2016 who had participated in the Guidance and Counseling field practice in schools. The number of research samples 65 students, sampling using techniquespurposive sampling. Collecting data using a Likert scale model questionnaire . Data were analyzed using descriptive statistical techniques. This study describes the readiness of students to become teachers of Guidance and Counseling in general in the high category, student readiness based on each aspect (1) the readiness of students based on the aspect of self-understanding is in the high enough category (41.5% ), (2) the readiness of students based on the competent aspect is in the high category (36.9%), (3) the readiness of students based on the aspects of psychological health is in the quite high category (49.2%), (4) the readiness of students based on the aspects of believed to be in the very high category (36.9%), (5) the readiness of students based on the aspect of being able to be warm was in the quite high category (30.8)%.